Dasatinib associated lymphadenopathy in a chronic myeloid leukemia patient: A case report. Issue 45 (6th November 2020) - Pilalas, Dimitrios; Koletsa, Triantafyllia; Arsos, Georgios; Panselinas, Grigorios; Exadaktylou, Paraskevi; Polychronopoulos, George; Savopoulos, Christos; Kaiafa, Georgia D.
Abstract: Rationale: Dasatinib associated lymphadenopathy (DAL) is a rare adverse event in chronic myeloid leukemia patients (CML). A case of voluminous lymphadenopathy in the context of DAL is presented. Patient concerns: A 40-year-old male patient was diagnosed with BCR-ABL1 positive chronic stage CML 2 years ago and achieved complete molecular response on nilotinib, which was switched to dasatinib due to nilotinib intolerance. After 5 months on dasatinib, the patient presented with a large mass in the axillary region. Diagnosis: Common infectious and autoimmune etiologies of lymphadenopathy were ruled out. The positron emission tomography/computed tomography (PET/CT) demonstrated a hypermetabolic lymphadenopathy highly suspicious of lymphoma. The subsequent biopsy excluded lymphoma or extramedullary blastic transformation of CML and revealed reactive lymphadenopathy with mixed (cortical and paracortical) pattern. Clinical history and clinicopathological correlation suggested the diagnosis of DAL. Intervention: Dasatinib was discontinued and the patient remained in close follow-up. TKI treatment with nilotinib was reinitiated. Outcomes: Lymphadenopathy resolved clinically at 4 weeks and normalization of PET/CT findings was documented at 9 weeks after cessation of the drug. TKI treatment with nilotinib was reinitiated with good tolerance. Lessons: DAL may present with voluminous lymphadenopathy consistent with malignancy in clinical and imaging workup. We describe the spectrum of lesions associated with DAL and identify common features with drug-induced lymphadenopathy.